Diseño de un sistema de tratamiento de residuos sólidos a partir de una trituradora en la cuidad de Riohacha (2020)
The present proposal has the general objective: to design a solid waste treatment system from a crusher in the Tourist and Cultural District of Riohacha, initially the environmental conditions represented in the volume of production of specifically plastic solid waste are established, as well as The processes and materials necessary for the design of the solid waste treatment system that allow a solution to the contamination problem in the context of interest are presented. Next, the structural components of the design are defined that will allow shredding several tons of plastic that will generate a positive impact in the region. From the creation of the design model, from the methodological aspect, a quantitative study is proposed to determine the production volume of solid waste and the capacity to decrease it from the crushing technique